Evaluation of Customer Satisfaction with Public Trans-portation in Yogyakarta - Findra Kartika Sari Dewi; Niko Guntara (International Journal of Data Science, Engineering, and Analytics, 2022)
Yogyakarta is one of the cities that provides public transportation facilities to support the activities of its people in traveling. However, the use of public transportation is still a little in demand in Yogyakarta, whether it's because the desired travel route is not available, the tariff is not reasonable, the driver is reckless, or the physical condition of the vehicle is no longer suitable for use. Usually, after people use public transportation, the satisfaction that has been felt will appear. Therefore, a sentiment analysis study will be conducted to determine the value of customer satisfaction on the use of public transportation in Yogyakarta. This research uses social media twitter to get data. The data will identify an opinion or problem from someone whether it tends to be positive, negative, or neutral. The author uses the SentiStrength method to classify tweet data to get a value. This study will produce a summary of customer satisfaction values ​​that can be used as a reference in increasing customer satisfaction so that people are more interested in using public transportation in Yogyakarta.